2021
DOI: 10.1016/j.jsurg.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Surgery Oral Board Examinations in the Era of COVID-19 Pandemic. How I Do It!

Abstract: Highlights The COVID-19 Pandemic has led to a profound disruption of on-campus and in-person educational activities. Many in-person didactics and examinations were canceled or rescheduled, including the American Board of Surgery-Certifying Exam (ABS-CE). In this study, we found that Virtual Mock Oral Examination (V-MOE) is feasible, accessible, and a potential alternative for in-person MOEs at a program level for ABS-CE preparation. It is an opportunity to collaborate with other residency prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Two multi-institutional studies focused on vascular and cardiothoracic surgery trainees, for example, found the virtual mock oral platform to be both feasible and useful for participants [ 17 , 18 ]. Similar pilot experiences have been published in the general surgery literature indicating that both faculty and trainee participants are satisfied with the experience and seek standardization of the process moving forward [ 19 , 20 ]. In these pilot studies, trainees were primarily evaluated with pass–fail case rubrics and written feedback.…”
Section: Introductionmentioning
confidence: 65%
“…Two multi-institutional studies focused on vascular and cardiothoracic surgery trainees, for example, found the virtual mock oral platform to be both feasible and useful for participants [ 17 , 18 ]. Similar pilot experiences have been published in the general surgery literature indicating that both faculty and trainee participants are satisfied with the experience and seek standardization of the process moving forward [ 19 , 20 ]. In these pilot studies, trainees were primarily evaluated with pass–fail case rubrics and written feedback.…”
Section: Introductionmentioning
confidence: 65%
“…Our successes have duplicated those with the general surgery VCE across all the various components surveyed and were consistent with the results reported for the two mock oral VCEs for vascular and general surgery trainees. 1 , 4 , 5 The incorporation of the images required both establishing a secure method for sharing the images and a mechanism by which the candidates could request additional images not provided in the initial stem. This required developing a strategy such that they did not know whether any additional images were available for each question.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that online assessment is a valid tool for assessing knowledge, and that it holds benefit to both the examiner and the candidate (13,15). The challenge lies in its implementation.…”
Section: Discussionmentioning
confidence: 99%